ISOLASI DAN KARAKTERISASI SENYAWA ALIFATIK TAK JENUH DARI KULTUR AKAR MORUS CATHAYANA - YUNIANTARI, NI; Holisotan Hakim, Euis (Jurnal Crystal : Publikasi Penelitian Kimia dan Terapannya, 2025)
Moraceae is a plant that is widely distributed in Asia and the Indopacific Islands. One of the genera of Moraceae that has been widely researched and whose bioactive compounds is the Morus, namely M. cathayana. the aim of this research is determining the diversity of secondary metabolite of root cultures of Morus cathayana. Isolation of secondary metabolites from Morus cathayana root cultures was using several chromatographic techniques and eluents combination is n-hexane, acetone, chloroform, ethyl acetate and methanol. In this research, the compound KMAC-4 was isolated. Characterization of the KMAC-4 compound using the FTIR ONE Perkin-Elmer spectrophotometer. showed that the KMAC-4 compound had an absorption at wave number (cm-1): 3654.97; 3650.45; 2936.87; 1718.71; 1465.76; 1381.56; 1049.50. Based on IR spectrum data that has been interpreted, analyzed and studied according to the phytochemical of the Morus, it can be concluded that the KMAC-4 is an unsaturated aliphatic compound which belongs to the steroid or terpenoid group.